Message from the Mermaid-Do not Miss the Anomaly Scan - Charu Sharma; Abhishek Bhardwaj; Siddesh RC; Anita Yadav; Senthil Kumar (JCDR Research and Publications Pvt. Ltd., 2017)
Sirenomelia, also known as Mermaid syndrome is a rare congenital structural anomaly, caused by a vascular insult during the embryonic life. It is characterized by varying degrees of fusion of the lower extremities along with urogenital and gastrointestinal malformations. Diagnosis of sirenomelia can be made as early as 11-13 weeks and hence the birth of this syndromic baby can be prevented. We report a case of Sirenomelia- Mermaid Syndrome along with the clinical autopsy findings and review its literature.